The Determinants of Understanding the Causes of High Cholesterol Levels in Employees - Pranitasari, Diah; Said, Meldasari; ., Dahlia; Gazali, Akhmad; Harini, Sri (KnE Social Sciences, 2023)
This study aimed to determine the factors that influenced an individual’s understanding of the causes of high cholesterol levels by looking at the characteristics of knowledge, attitudes, behavior, age and education level. Companies can use the results of this study for implementing occupational safety and health programs. The research was conducted at PT Kalimantan Prima Persada (KPP) Indonesia through questionnaires distributed to 76 employees. The results showed that knowledge, attitude, age and level of education did not affect the understanding of increasing cholesterol levels, but behavior did affect the understanding of the causes of increased cholesterol levels. Keywords: Cholesterol Levels, Employees, Occupational Health and Safety (OHS)